COUNTERPOINTS AND FUGUES IN MUSIC OF TĀLIVALDIS ĶENIŅŠ – PROFESSOR OF COUNTERPOINT AND FUGUE (Mūzikas akadēmijas raksti, 2024)
Tālivaldis Ķeniņš is one of the most significant Latvian composers who spent all their creative life in emigration. From the very beginning of his professional career contrapuntal texture and fugue became rather typical for his style. Jāzeps Vītols, his first teacher of counterpoint and fugue, estimated with the highest mark his examination tests in our conservatoire. However the young man was still scarcely grounded well in this field. The composer remembers that lessons of counterpoint and fugue were insufficient since managed without any analysis of classical music. The young composer continued his education in Parisian conservatoire where theoretical subjects were studied more seriously and deeper. The highest level of his comprehension of contrapuntal and fugal theory and history was reached later, in Toronto where he moved from Paris and became professor in the local university and conservatoire. It is really portentous that Tālivaldis Ķeniņš dealt with counterpoint and fugue very intensive all his life as a teacher and composer.